Incorporation of Herbal Plants in the Diet of Ruminants: Effect on Meat Quality - Odhaib, Kifah J; Al-Hajjar, Qabas N; Alallawee, Measem H A (The Iraqi Journal of Veterinary Medicine, 2021)
The use of herbal plants as food additives in animal nutrition to enhance meat processing efficiency and meat quality has been reviewed. Today, the consumer demand is safety, nutritive value, taste, uniformity, meat variety, and good appearance of meat products. Thus, to meet the consumers' demand, development of product and research should be improved. Studies have been shown that the use of herbs, spices, and their extracts are of the major interventions, which were adopted in the industry of the meat for improving its quality traits. In the present paper, the most recent literature about use of bioactive compounds in herbal plants for evaluating a number of parameters related to meat quality, including fat content and distribution, water content, water holding capacity, collagen content, pH, tenderness color, lipid oxidation and flavor were reviewed.